2014
DOI: 10.1142/s0218348x14500169
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Geometry of Equilibrium Payoffs in Discounted Supergames

Abstract: This paper examines the pure-strategy subgame-perfect equilibrium payoffs in discounted supergames with perfect monitoring. It is shown that the equilibrium payoffs can be identified as sub-self-affine sets or graph-directed iterated function systems. We propose a method to estimate the Hausdorff dimension of the equilibrium payoffs and relate it to the equilibrium paths and their graph presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In repeated games, the set of subgame-perfect equilibria can be defined recursively: a strategy profile is an equilibrium if certain equilibrium payoffs are available as continuation payoffs, and these continuation payoffs may be generated by means of other equilibrium strategy profiles. This construction has been presented for pure strategies in Abreu et al [1,2], where they give a fixed-point characterization of the set of equilibrium payoffs (see also [3][4][5][6][7][8][9][10][11][12]). …”
Section: Introductionmentioning
confidence: 99%
“…In repeated games, the set of subgame-perfect equilibria can be defined recursively: a strategy profile is an equilibrium if certain equilibrium payoffs are available as continuation payoffs, and these continuation payoffs may be generated by means of other equilibrium strategy profiles. This construction has been presented for pure strategies in Abreu et al [1,2], where they give a fixed-point characterization of the set of equilibrium payoffs (see also [3][4][5][6][7][8][9][10][11][12]). …”
Section: Introductionmentioning
confidence: 99%
“…, δ n on the diagonal. Now, we are ready to present the fixed-point characterization of equilibrium payoffs (Abreu et al 1986(Abreu et al , 1990Cronshaw and Luenberger 1994;Mailath and Samuelson 2006;Berg and Kitti 2014).…”
Section: Monotonicity Of Equilibriamentioning
confidence: 99%
“…Recently, Berg and Kitti (2015) have shown that the equilibrium paths consist of repeating fragments called elementary subpaths. This has provided a new methodology for analyzing the set of equilibria, computing the pure-strategy payoffs (Berg and Kitti 2013) and identifying the equilibrium payoffs as particular fractals (Berg and Kitti 2014). These papers assume that the punishment payoffs are known but it has turned out that the punishment paths may be very complicated and difficult to find in some games.…”
mentioning
confidence: 99%
“…Berg and Kitti [12] propose two measures to analyze the set of equilibria: the Hausdorff dimension measures the density of the payoffs, see also [14] for unequal discount factors, and the asymptotic growth rate measures the number of different equilibrium paths. These measures make it possible to compare equilibria for different discount factor values and between games, and they can be extended to stochastic games by modifying the graphs so that each node corresponds to playing one action profile.…”
Section: Propositionmentioning
confidence: 99%
“…Berg and Kitti [12] have developed this idea in repeated games, where it is shown that the equilibrium paths consist of repeating fragments called elementary subpaths. These subpaths offer a novel way of computing and analyzing the set of equilibria [13,14]. The pure-strategy payoffs can be identified as particular fractals called sub-self-affine sets, and their density can be measured by the Hausdorff dimension.…”
Section: Introductionmentioning
confidence: 99%